Iceland and European Union accession - the whaling issue - Davies, Peter G.G. (Georgetown International Environmental Law Review, 2011)
This article seeks to assess one of the important questions regarding Iceland’s potential accession to the EU, namely, whether Iceland could legitimately continue its whaling operations under current EU environmental law if it becomes a member of the regional economic integration organization